Optimal Conditions for Spore-bound Laccase Production from Local Isolate of Bacillus subtilis* - Majeed Abd Zaid, Ahmed; J. Hashim, Abdulkareem (Al-Qadisiyah Journal of Pure Science, 2017)
Fifty seven of bacterial isolates were isolated from different soils in different sites of Al Diwaniyah and Baghdad in Iraq using nutrient agar medium. The primary screening of bacterial isolates was done on nutrient agar by dropping a few drops of syringaldazine on bacterial colonies proved that, only 10 isolates were developed a pink color within 15 seconds. The secondary screening was done on nutrient broth using syringaldazine as enzyme substrate proved that the isolate 54 developed the highest spore-bound laccase activity (12.8) U/ml. The biochemical tests of bacterial isolate with highest laccase activity showed that the bacteria are Bacillus subtilis. The optimization studies revealed that the maximum laccase production was achieved when the production medium were at the following conditions: 3 days of incubation, temperature 37 ËšC, pH 7.0, copper sulphate 0.2 mM, glucose as carbon source 3%, Tryptone as nitrogen source 0.2% , Kcl 1mM and pyrogallol 1mM as enzyme inducer , after these conditions the spore-bound laccase activity was (439.23) U/ml.